Multicenter evaluation of neurofilaments in early symptom onset amyotrophic lateral sclerosis. (2nd January 2018) - Feneberg, Emily; Oeckl, Patrick; Steinacker, Petra; Verde, Federico; Barro, Christian; Van Damme, Philip; Gray, Elizabeth; Grosskreutz, Julian; Jardel, Claude; Kuhle, Jens; Koerner, Sonja; Lamari, Foudil; et al.
Abstract : Objective: To examine neurofilament (Nf) concentrations according to symptom onset and clinical diagnostic certainty categories of amyotrophic lateral sclerosis (ALS). Methods: We measured Nf light chain (NfL) and phosphorylated Nf heavy chain (pNfH) CSF and NfL serum levels in patients with ALS with first symptom onset ⩽6 months (n = 54) or >6 months (n = 135) from sampling, and patients with other neurologic diseases, differential diagnoses of a motor neuron disease (MND mimics), and other MND variants to determine the diagnostic accuracy in patients with ALS with early symptom onset. Samples were received multicentric and analyzed by ELISA and Simoa platform and related to other clinical measures. Results: NfL and pNfH in CSF and NfL in serum were increased in early and later symptomatic phase ALS ( p < 0.0001). CSF and serum NfL and CSF pNfH discriminated patients with ALS with early symptom onset from those with other neurologic diseases and MND mimics with high sensitivity (94%, 88%, 98%, and 89%, 100%, 78%) and specificity (86%, 92%, 91%, and 94%, 90%, 98%) and did not vary between clinical diagnostic categories of ALS in the early symptomatic phase group. Baseline NfL and pNfH levels were not significantly different in patients with ALS with clinical progression to definite or probable ALS at follow-up. Conclusion: The measurement of Nf has potential to enhance diagnostic accuracy of ALS in those presenting soon after symptom onset, and is measurable across multiple centers. Classification of evidence: This study provides Class II evidence that CSF and serum Nf concentrations discriminate ALS with early symptom onset from other neurologic diseases.